Estimation of structure, characterization and studying properties of novel CuNiSnSex nanocomposits (Eurasian Journal of Physics,Chemistry and Mathematics, 2021)
CunisnSe nanocomposits were successfully synthesized in this study using the nanometric approach. It possesses a monoclinic structure and a hexagonal phase, according to XRD diffraction data. The tiny crystal size of CunisnSe causes the XRD line to expand. However, the comparison determined a significant number of grid ratios. The The agglomerated and circular rectangular configurations nanocomposit were confirmed by FESEM pictures. The optimal energy gap, according to optical characteristics, is 1.25 e v. whech aids the thermoelctric performence of material or sorbeants in solar call aplications